Enduring Hypocrisy as ASEAN's Organisational Problem? - Ki-Hyun Bae (Journal of Current Southeast Asian Affairs, 2024)
This paper complements the limited scholarly interest in the case of the Association of Southeast Asian Nations (ASEAN)'s consistent practice of word–deed gaps, or “hypocrisy” according to some scholars, by employing the insights of organisational sociology. Specifically, it introduces a claim that the gap between ASEAN's words and deeds can be understood as an organisational response to its material and political vulnerability in relation to its major external stakeholders, aiming to ensure its survival and adaptability. Accommodating multiple, or sometimes even conflicting, demands from various external actors, ASEAN may be able to secure its material and diplomatic engagement in developmental and political regionalism within Southeast Asia. However, ASEAN also wants to protect its local identity and practices; or it may want to avoid forced internal reforms at an undesirable scale and pace. In this context, organised hypocrisy would likely become a vital consideration for the complex institution. For ASEAN, this paper notes, these word–deed gaps reflect the way it wants to manage conflicting external demands as an international social agency.